Social Policy, Social Democracy, and the Lessons of History: A Case Study of Gareth Stedman Jones' "An End to Poverty?" - Patriquin, Larry (Canadian Review of Social Policy / Revue canadienne de politique sociale, 1996)
Gareth Stedman Jones argues in An End to Poverty? A Historical Debate that it is important to reconsider Enlightenment thinkers, in particular Antoine-Nicolas de Condorcet and Thomas Paine, because they can inform current debates on social policy as well as contribute to a renewal of social democratic philosophy. In contrast, this article suggests that the proposals of these writers are of little value in addressing the contemporary challenge of eradicating poverty and are unhelpful in rethinking the central commitments of social democracy. This article will conclude with a brief examination of the lessons we can draw from Sweden, which has produced the most comprehensive welfare state in the advanced capitalist societies. Gareth Stedman Jones soutient dans son article An End to Poverty? A Historical Debate qu'il est important de revisiter les penseurs du Sigcle des lumigres, dont en particulier Antoine-Nicolas de Condorcet et Thomas Paine, parce qu'ils peuvent Cclairer les debats actuels sur la politique sociale et contribuer ainsi au renouveau de la philosophie social-democratique. Cet article suggsre, en revanche, que les propositions de ces Ccrivains n'ont que peu de valeur au sujet du defi contemporain de l'eradication de la pauvretC et ne sont d'aucun secours quand il s'agit de repenser les engagements fondamentaux de la social-dCmocratie. En conclusion, cet article examine brigvement les lefons h retenir de la Sukde qui a produit 1'~tat-providence le plus avancC des sociCt6s capitalistes progressistes.